Understanding trends in property-level rental inflation - Slaymaker, Rachel; Banahan, Conor; Kren, Janez (ESRI, 2025)
This report provides a detailed analysis of rental price developments at the individual property level, using the first three years of annual registration data from the Residential Tenancies Board (RTB). Unlike the RTB/ESRI Rent Index, which reflects growth in the average rent level in the market and is influenced by property churn, this study tracks the same properties over time to capture the household experience of rental inflation. The analysis covers over 375,000 matched property pairs between Q2 2022 and Q1 2025, offering unique insights into how rents for the same unit evolve over time, the degree of price stickiness, turnover effects and differences between Rent Pressure Zones (RPZ) compared to non-RPZ areas. The findings highlight a moderation in property-level rental inflation during the latest year (Q2 2024–Q1 2025), alongside notable differences between RPZs and non-RPZ areas, and between properties with ongoing tenancies and those with tenant turnover. Key findings: Nationally, property-level rents grew moderately, by an average of 2.15% per annum in the latest year, down from 2.7% one year earlier. 62% of properties saw no change in rent year-on-year, a rise of 4.8 percentage points on the previous year. Rent increases were notably lower for properties in RPZs, especially at tenancy turnover: Ongoing tenancies: 1.0–1.4% in Dublin, 1.1–1.6% in other RPZs, versus 2.9–4.4% in non-RPZs. Turnover properties: 1.7–2.7% in Dublin, 3.6–5.2% in other RPZs, versus 11.6–15.9% in non-RPZs. In response to tighter HICP-linked rent caps there is evidence of reduced clustering at 2% and more smaller increases (>0–2%), suggesting landlords adjusted behaviour to tighter caps. However, many still applied a flat 2% rise. The largest property-level rent increases occurred in the north/north-west of the country in the latest year, as well as selected counties like Kerry and Tipperary: Ongoing tenancies: 4.0–5.1% on average in Kerry, Roscommon, Leitrim, Longford, Cavan, Donegal versus 1.1% in Dublin. Turnover properties: 14–18.3% on average in Kerry, Tipperary, Leitrim, Longford, Cavan, Monaghan, Donegal versus 2.3% in Dublin. In Dublin, the largest landlords (>100 properties) were less likely than small landlords (1–2 properties) to leave rents unchanged for ongoing tenants, yet at tenancy turnover they were much less likely to apply increases above 4%. These landlords also recorded the biggest rise in unchanged rents compared to last year, likely reflecting tighter HICP-linked caps and possibly a greater awareness of RPZ rules. How this complements the RTB/ESRI Rent Index: The RTB/ESRI Rent Index provides market-level surveillance, measuring changes in standardised average rent levels across the private rental sector. These figures reflect broader market pressures and are influenced by both individual property rent changes and market churn (where properties enter or exit the market, often at different price levels than the existing stock). Structural factors such as limited rental supply, high construction costs, and financing challenges also affect Rent Index trends. In contrast, this property-level analysis captures the household experience of rental inflation, showing how rents change for the same property over time. This reveals modest rent growth compared to the Rent Index and highlights the role of RPZs in limiting price rises.